Does the equity market reward "superior" management earnings forecast? Evidence from the U.S. quarterly earnings guidance / Tina Wang - Wang, Tina (Universiti Teknologi MARA, 2021)
This paper examines whether equity markets reward the controversial practice of issuing short-term management earnings forecasts. Using a large sample of quarterly earnings forecasts, this research found that firms may temporarily reduce stock price volatility by issuing quarterly earnings forecasts. Furthermore, the analysis showed that not all guidance issuers are equally rewarded by equity capital markets. The benefits of reduced stock price volatility and favorable market valuation primarily accrue to firms with a track record of supplying accurate and timely short-term earnings forecasts. Findings suggest that superior short-term earnings guidance, which fosters transparent financial information environments and reduces investor information uncertainty, is indeed rewarded by equity capital markets. As limited research examines the association between forecast attributes and the capital market consequences of quarterly earnings guidance, this study aimed to provide empirical evidence on equity capital market rewards by issuing high-quality quarterly earnings guidance. A practical implication is that firms need to invest in accounting information systems and accounting talent in order to achieve capital market benefits of supplying high-quality short-term earnings forecasts.